Body weight, perceived weight stigma and mental health among women at the intersection of race/ethnicity and socioeconomic status: insights from the modified labelling approach. Issue 1 (4th October 2017) - Ciciurkaite, Gabriele; Perry, Brea L.
Abstract: With increasing rates of obesity in the United States, attention to life chances and psychological consequences associated with weight stigma and weight‐based discrimination has also intensified. While research has demonstrated the negative effects of weight‐based discrimination on mental health, little is known about whether different social groups are disproportionately vulnerable to these experiences. Drawing on the modified labelling theory, the focus of this paper is to investigate the psychological correlates of body weight and self‐perceived weight‐based discrimination among American women at the intersection of race/ethnicity and socioeconomic status (SES). Analyses use data from the National Health Measurement Study (NHMS), a national multi‐stage probability sample of non‐institutional, English‐speaking adults, ages 35 to 89 in 2005–2006. Our findings demonstrate that the effect of weight‐based discrimination on psychological well‐being is highly contingent on social status. Specifically, the psychological consequences of discrimination on Hispanic women and women in the lowest household income group is significantly greater relative to White women and women with higher household income, controlling for obesity status and self‐rated health. These results suggest that higher social status has a buffering effect of weight stigma on psychological well‐being.